THE EFFECT OF JOURNAL WRITING TECHNIQUE ON STUDENTS’ WRITING ABILITY - Eliwarti; Purwanti, Indah Tri (International Journal of Educational Best Practices, 2021)
This quasi-experimental research aims at looking at the effect of Journal Writing technique on the ability in writing a paragraph. Specifically, the research answers the research questions about the students’ ability in writing, the effect of Journal Writing technique on the students’ ability in writing, and the students’ attitude toward Journal Writing technique applied in their Writing class. The sample are one class from the second semester of English Department students in 20172018 academic year. The data were collected through writing tests and the distribution of a set of questionnaires. From the results, nearly 60% of students’ ability in writing is at Average to Good level before the treatment. After the treatment, 56.76% of their ability is at Good to Excellent level. To test whether the increased score is statistically significant or not, the data were analyzed using t-test. Having t-obs (8.26) which is higher than t-table (2.030), there is a plausible reason to believe that the teaching of writing using Journal Writing technique significantly affects the students’ ability in writing paragraph. The data from questionnaire showed nearly 64% students have ‘high’ attitude toward Journal Writing technique applied in their class.